2009
DOI: 10.1111/j.1471-4159.2009.06196.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C epsilon activation delays neuronal depolarization during cardiac arrest in the euthermic arctic ground squirrel

Abstract: During the pre-hibernation season, arctic ground squirrels (AGS) can tolerate 8 min of asphyxial cardiac arrest (CA) without detectable brain pathology. Better understanding of the mechanisms regulating innate ischemia tolerance in AGS has the potential to facilitate the development of novel prophylactic agents to induce ischemic tolerance in patients at risk of stroke or CA. We hypothesized that neuroprotection in AGS involves robust maintenance of ion homeostasis similar to anoxiatolerant turtles. Ion homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 65 publications
(163 reference statements)
5
58
1
Order By: Relevance
“…Hibernators naturally tolerate severe reductions in cerebral blood flow during torpor [51,52]. For example, our laboratory previously observed that arctic ground squirrels (Urocitellus parryii) are remarkably tolerant to global cerebral ischemia during euthermia [53,54]. Massive protein SUMOylation (including increased SUMO signal in cell nuclei) is reported to occur during torpor in 13-lined ground squirrels (Spermophilus tridecemlineatus) [52].…”
Section: Sumoylationmentioning
confidence: 99%
“…Hibernators naturally tolerate severe reductions in cerebral blood flow during torpor [51,52]. For example, our laboratory previously observed that arctic ground squirrels (Urocitellus parryii) are remarkably tolerant to global cerebral ischemia during euthermia [53,54]. Massive protein SUMOylation (including increased SUMO signal in cell nuclei) is reported to occur during torpor in 13-lined ground squirrels (Spermophilus tridecemlineatus) [52].…”
Section: Sumoylationmentioning
confidence: 99%
“…It would also be of interest to test fossorial species other than mole-rats under the same conditions. As noted above, hippocampal slices from arctic ground squirrels have significantly delayed electrophysiological responses to combined oxygen and glucose deprivation, compared to rats (Dave et al, 2009).If the neoteny hypothesis for hypoxia tolerance in naked mole-rat brain holds up under further mechanistic and comparative scrutiny, it may explain some other, seemingly unrelated, unusual traits of these animals. For example, peripheral insensitivity to chemical irritants (LaVinka et al, 2009), lack of a functional substance P nociceptive pathway (Park et al, 2003), poor thermoregulation (Buffenstein and Yahav, 1991), absence of fur, and high-affinity hemoglobin (Johansen et al, 1976) may all be juvenile characteristics retained into adulthood.…”
mentioning
confidence: 97%
“…The selective peptide inhibitor of εPKC (eV1-2) shortened the time to ID in brain slices from AGSs but not in rats even though εV1-2 decreased activation of εPKC in brain slices from both species. Activation of εPKC inhibits Na + /K + ATPase and voltage-gated sodium channels Nowak et al, 2004), both of which contribute to the collapse of ion homeostasis during ischemia and may be targets of εPKC during cerebral ischemia in AGSs (Dave et al, 2009). Blocking or delaying the ID can significantly improve recovery (Anderson et al, 2005;Takeda et al, 2003).…”
Section: Resistance To Ischemia/reperfusion In the Euthermic State Inmentioning
confidence: 99%
“…An increase in adenosine levels, in addition to bradykinin and opioids, initiate a series of intracellular signaling events via G-protein-coupled receptor signaling leading to activation of PKC activation (Di-Capua et al 2003). Several studies have shown that injections of adenosine could protect neuronal cells against hypoxic-type injury via a PKC-mediated mechanism (Dave et al 2009). A series of intracellular signaling that leads to the adenosine-mediated PKC-induced mechanism of hypoxia protection include; i) adenosine stimulates G-proteincoupled receptors, such as the A1/A3 adenosine receptors which activate phospholipases (phospholipase C; PLC) via G-proteins (Gi/o).…”
Section: Adenosine Facilitates Hypoxia Neuroprotection By Mediating Imentioning
confidence: 99%
“…This is important because PKC activity has been implicated in cell injury in the cerebral brain (Bright et al 2008)indicating that it could be involved in a conserved hypoxia response pathway. εPKC activation delays the collapse of ion homeostasis during ischemia in arctic ground squirrels (Dave et al 2009). This finding suggests that εPKC mediates 26 collapse of ion homeostasis in Arctic Ground Squirrels.…”
Section: Adenosine Facilitates Hypoxia Neuroprotection By Mediating Imentioning
confidence: 99%